Does biofilm formation have different pathways in Staphylococcus aureus? - Ali Shivaee; behroz sadeghi kalani; Malihe Talebi; Davood Darban-Sarokhalil (Iranian Journal of Basic Medical Sciences, 2019)
Objective(s): Biofilm formation is one of the most important factors in the development of infections caused by Staphylococcus aureus. In this study, the expression levels of genes responsible for biofilm formation were studied in methicillin sensitive and methicillin resistant S. aureus. Materials and Methods: A total of 100 meticillin-resistant s.aureus (MRSA) and meticillin-sensetive s.aureus (MSSA) isolates were studied. Bacterial biofilm formation was evaluated phenotypically using microtiter plate method. Real-time PCR tests were conducted to determine the expression levels of genes involved in biofilm formation. Results: Quantitative biofilm formation test was repeated three times for each specimen. The prevalence of weak, medium, and strong biofilm producers were 16%, 49%, and 35%, respectively. In MSSA isolates, expression levels of ica genes increased compared to the fnbA, fnbB, clfA and clfB genes. These results were different in MRSA isolates, and ica genes showed a decreased gene expression levels compared to the aforementioned genes.   Conclusion: Considering the results of this study, clf genes probably contribute to the same extent in both MRSA and MSSA isolates, and there is probably no significant difference in the role of these genes in these isolates. In addition, the results of this study indicated that MRSA may not use the conventional route for biofilm formation and may use independent pathways through Polysaccharide intercellular adhesion (PIA).